The Effect of Flexibility Training Using Proprioceptive Neuromuscular Facilitation (Pnf) on The Improvement of Flexibility and Accuracy Oo Mawashi Kick Performance in Karate Athletes - Muhammad Rey Farandi; Sagitarius; Patriana Nurmansyah Awwaludin (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to examine the effect of flexibility training using proprioceptive neuromuscular facilitation on increasing the flexibility and accuracy of karate athletes' mawashi kicks. To determine the effect of proprioceptive neuromuscular facilitation flexibility training on increasing the flexibility and accuracy of karate athletes' mawashi kicks, related to the data obtained by the author, it was measured using a side split instrument and point target with a total of 10 athletes to measure the level of flexibility and kick points obtained by athletes. The methods used in this study are to test statistical data, normality tests, and Paired Sampled T-Test. After testing the Pre-Test and Post-Test values, the results of the study showed that the sig value for Side Split was at 0.000 while the sig value for Point Target was at 0.027. From both sig results, it was concluded that the sig value. both were below 0.05, so it can be concluded that there is an effect of flexibility training using PNF on increasing the flexibility and accuracy of mawashi kicks.